2017
DOI: 10.21608/ejb.2017.10184
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hepatotoxic and Synergistic Effects of Sesame Oil With Methotrexate in Adjuvant Induced Arthritis

Abstract: Methotrexate (MTX) is the first-line agent for rheumatoid arthritis (RA) treatment although it causes hepatotoxicity leading to poor compliance to therapy. Sesame oil is unique due to its unusually high oxidative stability and anti-inflammatory property that attributed mainly to the presence of α-tocopherol and anti-oxidative sesame lignans. These components give sesame oil extraordinary high oxidative stability and anti-inflammatory property. The present study aimed to investigate the anti-hepatotoxic and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…A number of reports stated that SO showed the antiinflammatory effect through reduction of proinflammatory cytokines (e.g., TNF‐α, IL‐6, IL‐1α, and IL‐1β) as well as antioxidative effect either reduction of ROS or induction of antioxidative enzymes (GSH, NADPH oxidase, and GPx; Hsu, Chu, & Jou, b; Hsu, Chu, Li, & Liu, ; Kang, Naito, Tsujihara, & Osawa, ; Nakano et al, ; Narasimhulu et al, ; Narasimhulu, Riad, & Parthasarathy, ; Figure ). Ali, Atia, El Allawy, and Alla () showed that SO significantly decreased the levels of inflammatory mediator TNF‐α and IL‐6, although the levels of antiinflammatory mediator IL‐10 were significantly amplified in groups treated with combination of SO with MTX (first line antiarthritis agent) compared with group treated with SO only or MTX only in adjuvant‐induced arthritis rat model (Ali et al, ). Later, Ismail, Hasan, El‐Orfali, Ismail, and Khawaja () reported that daily oral administration of Δ9‐THC/SO combination, over a period of 21 days, attenuated erythrocyte sedimentation rate scores and proinflammatory cytokines, including TNF‐α, IL‐1β, and IL‐6 levels, to normal values and MTX‐treated values on adjuvant‐induced arthritis rat model (Ismail et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of reports stated that SO showed the antiinflammatory effect through reduction of proinflammatory cytokines (e.g., TNF‐α, IL‐6, IL‐1α, and IL‐1β) as well as antioxidative effect either reduction of ROS or induction of antioxidative enzymes (GSH, NADPH oxidase, and GPx; Hsu, Chu, & Jou, b; Hsu, Chu, Li, & Liu, ; Kang, Naito, Tsujihara, & Osawa, ; Nakano et al, ; Narasimhulu et al, ; Narasimhulu, Riad, & Parthasarathy, ; Figure ). Ali, Atia, El Allawy, and Alla () showed that SO significantly decreased the levels of inflammatory mediator TNF‐α and IL‐6, although the levels of antiinflammatory mediator IL‐10 were significantly amplified in groups treated with combination of SO with MTX (first line antiarthritis agent) compared with group treated with SO only or MTX only in adjuvant‐induced arthritis rat model (Ali et al, ). Later, Ismail, Hasan, El‐Orfali, Ismail, and Khawaja () reported that daily oral administration of Δ9‐THC/SO combination, over a period of 21 days, attenuated erythrocyte sedimentation rate scores and proinflammatory cytokines, including TNF‐α, IL‐1β, and IL‐6 levels, to normal values and MTX‐treated values on adjuvant‐induced arthritis rat model (Ismail et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Oral administration of rats suffering from rheumatoid arthritis, with sesame oil (1 mL/kg) and methotrexate (MTX) (1 and 2 mg/kg) reduced IL‐6, and TNF‐α also increased the amount of IL‐10 (Ali et al, 2017). In another study, in rats suffering from rheumatoid damage induced with injection of complete Freund's adjuvant in the left foot, oral administration of dronabinol (Δ9‐THC)/sesame oil, 2.5 mg/kg for 21 days decreased the deposition of erythrocytes and inflammatory cytokines, including TNF‐α, IL‐6, and IL‐10.…”
Section: Atherosclerosismentioning
confidence: 99%